Measuring Women’s Goal Setting and Decision-Making - World Bank (World Bank, Washington, DC, 2021)
Improving women’s agency is crucial for advancing gender equality. Less than half of women in Sub-Saharan Africa and South Asia participate in making decisions over their own health care, major household purchases, and visiting their families. Improving women’s ability to define goals and act on them is an important - and urgent - policy goal. Yet the understanding of how to achieve this goal is hampered by the lack of adequate measurement tools and recognized best practices. Research is needed to broaden and deepen the measurement of women’s goal setting and decision-making, both within and outside the household. This brief summarizes existing knowledge gaps in the two measurement areas and lays out how the measures for advancing gender equality (MAGNET) initiative plans to tackle them.